Update from the 2011 International Schwannomatosis Workshop: From genetics to diagnostic criteria12. Issue 3 (7th February 2013) - Plotkin, Scott R.; Blakeley, Jaishri O.; Evans, D. Gareth; Hanemann, C. Oliver; Hulsebos, Theo J.M.; Hunter‐Schaedle, Kim; Kalpana, Ganjam V.; Korf, Bruce; Messiaen, Ludwine; Papi, Laura; Ratner, Nancy; Sherman, Larry S.; et al.
Abstract Schwannomatosis is the third major form of neurofibromatosis and is characterized by the development of multiple schwannomas in the absence of bilateral vestibular schwannomas. The 2011 Schwannomatosis Update was organized by the Children's Tumor Foundation (www.ctf.org) and held in Los Angeles, CA, from June 5–8, 2011. This article summarizes the highlights presented at the Conference and represents the "state‐of‐the‐field" in 2011. Genetic studies indicate that constitutional mutations in the SMARCB1 tumor suppressor gene occur in 40–50% of familial cases and in 8–10% of sporadic cases of schwannomatosis. Tumorigenesis is thought to occur through a four‐hit, three‐step model, beginning with a germline mutation in SMARCB1 (hit 1), followed by loss of a portion of chromosome 22 that contains the second SMARCB1 allele and one NF2 allele (hits 2 and 3), followed by mutation of the remaining wild‐type NF2 allele (hit 4). Insights from research on HIV and pediatric rhabdoid tumors have shed light on potential molecular pathways that are dysregulated in schwannomatosis‐related schwannomas. Mouse models of schwannomatosis have been developed and promise to further expand our understanding of tumorigenesis and the tumor microenvironment. Clinical reports have described the occurrence of intracranial meningiomas in schwannomatosis patients and in families with germline SMARCB1 mutations. The authors propose updated diagnostic criteria to incorporate new clinical and genetic findings since 2005. In the next 5 years, the authors expect that advances in basic research in the pathogenesis of schwannomatosis will lead toward clinical investigations of potential drug therapies. © 2013 Wiley Periodicals, Inc.